Jejaring Kebijakan Pariwisata Berkelanjutan: Studi Strategi Pengelolaan Ekowisata di Kota Tasikmalaya - Riki Satia Muharam; Budiman Rusli (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Sustainable ecotourism management requires the involvement of various stakeholders through an effective policy network. The city of Tasikmalaya has significant ecotourism potential but still faces several management challenges, such as limited infrastructure, lack of coordination between institutions, and insufficient community participation in ecotourism policies. This study analyzes the role of policy networks in supporting sustainable ecotourism management in Tasikmalaya by highlighting the synergy between the government, the tourism industry, academics, and local communities. The analysis results indicate that government regulations, village tourism programs, and partnerships with the private sector and communities significantly impact ecotourism sustainability. However, challenges remain in policy implementation, such as overlapping regulations and a lack of support for conservation-based ecotourism innovation. Therefore, strategies that can be implemented to strengthen policy networks include participatory regulation improvement, enhanced cross-sector collaboration, and the utilization of technology for ecotourism policy monitoring and evaluation. With the right strategies, Tasikmalaya can optimize ecotourism management that not only enhances local economic welfare but also preserves environmental and cultural sustainability.